HISTORY OF UZBEK AND GEORGIAN CINEMA COOPERATION IN THE 40S-60S OF THE 20TH CENTURY - Farkhod Adilov (Social science and innovation, 2023)
This article describes the history of Uzbek-Georgian film cooperation in the 40s-60s of the 20th century, and provides detailed information about a number of films shot in cooperation between Uzbek and Georgian filmmakers.